Early Supported Discharge and Transitional Care Management After Stroke: A Systematic Review and Meta-Analysis - Jee, Sungju; Jeong, Minah; Paik, Nam-Jong; Kim, Won-Seok; Shin, Yong-Il; Ko, Sung-Hwa; Kwon, In Sun; Choi, Bo Mi; Jung, Yunsun; Chang, Wonkee; Sohn, Min Kyun (Frontiers in Neurology, 2022)
Objective: To investigate the available evidence on early supported discharge (ESD) and transitional care (TC) delivery service in patients with cerebrovascular disease Methods: A systematic literature search was conducted to collect all available evidence on the use of ESD and TC services. We included cluster-randomized pragmatic trials or randomized controlled trials (RCTs) that recruited patients with stroke or transient ischemic attack to receive either conventional care or any care service intervention that included rehabilitation or support provided by professional medical personnel with the aim of accelerating and supporting home discharge. Relevant data were electronically searched through international databases (Cochrane Library, EMBASE, and PubMed) and incorporated into a summary grid to investigate research outcomes and provide a narrative synthesis. Furthermore, we compared the outcomes in terms of length of hospital stay, patient and caregiver outcomes, and mortality through meta-analysis. Results: We identified and included a total of 20 publications of various original randomized studies. There were 18 studies conducted in western countries and 2 in eastern countries. The meta-analysis revealed a tendency that ESD or TC could decrease the length of hospital stay more than the usual care [standardized mean difference (SMD) -0.13; 95% confidence interval (CI) -0.31 to 0.04 days; P =0.14]. Moreover, there was a tendency that ESD resulted in better activities of daily living (ADL) than usual care (SMD 0.29; 95% CI -0.04 to 0.61; P=0.08). Patient outcome based on modified Rankin scale (mRS) score (SMD -0.11; 95% CI -0.38 to 0.17; P=0.45) and mortality [odds ratio 0.80; 95% CI 0.56 to 1.17; P=0.25] did not reveal any significant difference. The Caregiver Strain Index revealed no difference. Conclusion: We did not find a large effect size for the use of TC and ESD. When implementing the TC and ESD model from western to Asian countries, services should be prepared and implemented in accordance with national medical rehabilitation pathways for cerebrovascular disease.